(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2007)
Polypore mushroom was found to be rich in protein, fiber and cellulose. Polypore mushroom is found to grow on rotting hard wood logs. So, attempt was made to cultivate the species in laboratory condition. The present paper describes the process of cultivation of polypore mushroom in laboratory condition. The selected substrates (e.g. mango saw dust, rice hull, different kinds of wood chips, etc.) were mixed with calcium carbonate and water in a specific ratio, fermented and then placed in polypropylene bags. The bags weighed 500 g each. Locally isolated polypore mushroom mycelium were used as inoculum. The desired result was obtained with Garjan and Segun spawn bags. Some of the bags had perforations and the others were cut into one half of a circle. The production of polypore mushroom was about 12.3 g/ bag in perforated ones and about 13.9 g/bag in the other. The cultivated polypore mushroom species was found to be rich in fiber (28.9 g %), protein (16.9 g %) and cellulose (54.5 g %). No adverse effect was recorded when crude extract of polypore mushroom species was administered orally to rats (Long evans) with their normal diet. Bangladesh J. Sci. Ind. Res. 42(2), 115-120, 2007